2017
DOI: 10.1039/c7py01613a
|View full text |Cite
|
Sign up to set email alerts
|

The power of the ring: a pH-responsive hydrophobic epoxide monomer for superior micelle stability

Abstract: We developed micelles with superior stability by integrating a novel hydrophobic, pH-responsive epoxide monomer, tetrahydropyranyl glycidyl ether.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 70 publications
2
41
0
Order By: Relevance
“…A critical micelle concentration of 0.014 mg mL −1 was determined for PEG 40 ‐ b ‐PEEGE 25 (wt% of EEGE = 66.7%) by using DPH as fluorescent probe ( Figure ) . This value is in good agreement with the CMC value of 0.0103 mg mL −1 which has been determined by using pyrene as fluorescent probe in a recent paper by Song et al for PEG 114 ‐ b ‐PEEGE 60 (wt% of EEGE = 63.2%) . This value is of the same order of magnitude as those of commonly studied PEG‐PCL copolymers, indicating a good stability of the micelles …”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…A critical micelle concentration of 0.014 mg mL −1 was determined for PEG 40 ‐ b ‐PEEGE 25 (wt% of EEGE = 66.7%) by using DPH as fluorescent probe ( Figure ) . This value is in good agreement with the CMC value of 0.0103 mg mL −1 which has been determined by using pyrene as fluorescent probe in a recent paper by Song et al for PEG 114 ‐ b ‐PEEGE 60 (wt% of EEGE = 63.2%) . This value is of the same order of magnitude as those of commonly studied PEG‐PCL copolymers, indicating a good stability of the micelles …”
Section: Resultssupporting
confidence: 80%
“…After this work‐up, no phosphazenium traces were detectable on 1 H and 13 C NMR spectra (Figure C and Figure S1, Supporting Information). According to Kim and co‐workers, a EEGE X n of 22 in the PEG‐PEEGE block copolymers provides micelles that are not toxic against HeLa cells, up to 500 µg mL −1 . The polymerization degree ( X n ) of the PEEGE block was set to 25, 15, and 5 to ensure a good biocompatibility of the mPEG‐ b ‐PEEGE micelles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Independently from previous research, our group reported the preparation of TPGE modulate the hydrolysis rate of the acetal linker ( Figure 12 a). [ 26 ] 3,4‐Dihydropyran (a widely utilized protecting group for alcohols) was used to shield the free hydroxyl group of glycidol, which resulted in the TPGE monomer at a high yield. As TPGE is a hydrophobic moiety, amphiphilic polymers can easily be prepared through its block copolymerization initiated with m PEG (Figure 12b).…”
Section: Glycidyl Ethers With An Acetal Moietymentioning
confidence: 99%
“…After the successful introduction of the EEGE monomer, various types of acetal‐based monomers have been employed in the synthesis of polyethers, including 1,2‐isopropylidene glyceryl glycidyl ether (IGG), [ 23 ] catechol acetonide glycidyl ether (CAGE), [ 24 ] 1‐(glycidyloxy)ethyl ethylene glycol ether (GEGE), [ 25 ] tetrahydropyranyl glycidyl ether (TPGE), [ 26 ] tetrahydrofuranyl glycidyl ether (TFGE), [ 26,27 ] and cyclohexyloxy ethyl glycidyl ether (CHGE) [ 28 ] ( Figure 1 ). These monomers not only utilized as protecting groups for hydroxyl groups under AROP conditions but also used as pH‐responsive moieties in biomedical applications, further expanding their utility in the use of functionalized polyethers.…”
Section: Introductionmentioning
confidence: 99%